Interpretation of Verses About the Story of the People of Prophet Shu’aib in Jāmi' al-Bayān Fī Ta'wīl Al-Qur'ān: Analysis of the Moral Character of The People of Madyan - Rizka Amanda Wulandari; Kiki Muhamad Hakiki; Beko Hendro (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2025)
This article examines the interpretation of verses related to the story of the people of Prophet Shu'aib in the Jāmi' Al-Bayān Fī Ta'wīl Al-Qur'ān. The focus of this study is directed at analyzing the moral character of the people of Madyan so that there is an ibrah (moral message) contained in the story of the people of Prophet Shu'aib. The verses that discuss the story of the people of Madyan are QS. al-A'raf 85-94, QS. Hud 84-94, QS. asy-Syu'ara' 176-191 and QS. al-Ankabut 36-37 using ath-Thabari's interpretation. The purpose of this study is to examine and review the interpretation of the verses of the Qur'an containing the story of the people of Prophet Shu'aib from the perspective of Jāmi' al-Bayān Fī Ta'wīl Al-Qur'ān by Imam Ath-Thabari and to explore the moral aspects of the story of the people of Madyan. This research is classified as library research related to library studies, focusing on the character of the people of Madyan. Thus, the conclusion shows that the story of the people of Prophet Shu'aib contains lessons that can be used as life lessons, namely positive characters such as honesty and justice, belief in the truth, tolerance, and humility.